LOWER SEMICONTINUITY of PULLBACK ATTRACTORS FOR A SINGULARLY NONAUTONOMOUS PLATE EQUATION - da Silva, Ricardo Parreira [UNESP] (Texas State Univ, 2012)
We show the lower semicontinuity of the family of pullback attractors for the singularly nonautonomous plate equation with structural dampingu(tt) + a(t, x)u(t) + (-Delta)u(t) + (-Delta)(2)u + lambda u = f(u),in the energy space H-0(2)(Omega) x L-2(Omega) under small perturbations of the damping term a.
Keywords: Pullback attractors; nonautonomous systems; plate equation; lower-semicontinuity